Knowledge, attitudes, and practices toward halitosis among dental patients at Zewditu memorial hospital, Addis Ababa, Ethiopia - Degif, Rediet; Abaynew, Yeshewas (Frontiers in Oral Health, 2025)
BackgroundBad breath, or halitosis, is a common oral health problem that can significantly affect a person's social and psychological well-being. Understanding dental patients' knowledge, attitudes, and practices related to halitosis provides valuable insights into the current state of KAP related to halitosis in Addis Ababa and highlights the need for targeted educational interventions within dental health services.ObjectiveThis study aimed to assess the knowledge, attitudes, and practices toward halitosis among dental patients at Zewditu Memorial Hospital in Addis Ababa, Ethiopia.MethodsAn institution-based cross-sectional study design was employed. A systematic random sampling technique was used to select 214 study participants. Data were collected via a structured questionnaire that assessed the participants’ knowledge, attitudes, and practices related to halitosis. The data were checked, cleaned, and entered into SPSS version 25.0. Descriptive statistics were used to describe the data, and the findings were presented in texts, tables, and graphs.ResultsIn terms of knowledge, 71% of the participants had poor knowledge about halitosis. Approximately 68.7% of the participants had an unfavorable attitude toward halitosis. Furthermore, while 40.7% of the participants reported regular oral care and 42.5% used mouthwash, only 26.6% of the participants reported good practices regarding halitosis.ConclusionOverall, knowledge, attitudes, and practices regarding halitosis among dental patients at Zewditu Memorial Hospital were not satisfactory. These results highlight critical gaps in public awareness and effective management strategies for halitosis. This study highlights the need for integrated public health initiatives and clinical practices that focus on improving awareness and management of halitosis to ultimately promote better oral health in the community.